STRATEGI GURU DALAM PEMBELAJARAN MATEMATIKA SD KELAS IV DI MASA PANDEMI COVID-19 - MUHAMMAD YUSRIL HASAN; MUHAMMAD AGUSTIYAN; PANUT SETIONO; NANI YULIANTINI; WURJINEM WURJINEM (Jurnal Ilmiah Pendidikan Guru Sekolah Dasar, 2022)
Learning that is carried out online or online currently has many obstacles, one of which is in explaining mathematics material which is actually abstract. Grade IV elementary school students are vulnerable to the age of 8-9 years, which is where they are still in the concrete operational stage. The purpose of this study was to obtain information about teacher strategies in teaching high-grade elementary school mathematics (Class IV) during the current Covid-19 pandemic. This research method is a qualitative research method of exploratory study using interviews and literature study. The results of this study are that there is no specific strategy for teachers in teaching high-grade mathematics, the teacher relies on the WhatsApp Group application to send material explanation videos, record material voice or assignment explanations, and do not forget that the teacher also inserts motivational words for students.